Analisis Deskriptif Layanan Infeksi Menular Seksual (IMS) dan Voluntary Counselling and Testing (VCT) di Klinik Griya ASA - Hidayat, Muhamad Taufik (Nur Science Institute and Perkumpulan Keluarga Berencana Indonesia (PKBI) Semarang, 2024)
Background: This descriptive quantitative study analyzed secondary data from the Sexually Transmitted Infection (STI) and Voluntary Counselling and Testing (VCT) services at Griya ASA Clinic, PKBI Semarang, from July 2013 to March 2014. The study aimed to describe the service performance and assess the effectiveness of outreach and referral programs in controlling STI and HIV transmission among key populations. Method: Data were obtained from monthly STI and VCT reports, including individual service records and population statistics of female sex workers (FSWs) in Argorejo. Descriptive analysis was applied using frequency tables and visual diagrams to examine service trends, demographic characteristics, and case findings. Result: Results show that clinic visits for both STI and VCT services remained low, especially among non-FSW clients. Only 0.9% of VCT clients were HIV positive, and 25% of STI clients tested positive. Service coverage among Argorejo FSWs reached 14.43% for STI and 51.5% for VCT. Implication: These findings indicate a need to strengthen outreach, referral, and cross-sector collaboration, as well as to integrate data systems such as SIHA and CMIS. The study provides baseline evidence for improving community-based HIV and STI service performance in local clinical settings.